(untitled) (La Rivada, 2025)
The sexual division of labor preferentially assigns women responsibility for domestic and caregiving tasks, which they combine with productive activities. Such distribution takes on specific charactersitcs in rural areas which generate gender inequalities that are important to identify and analyze. For this reason, we conducted a study on who is responsible for paid and unpaid work in family farming, and how these tasks are distributed throughout the day. As part of this study, we conducted a time-use survey with a sample from the province of Buenos Aires. The results show that women are primarily responsible for domestic and caregiving work, performing them under precarious living conditions, and that men are included in these activities even though they do not include them in their activity diaries. This finding allows for reflection on men’s narratives and practices, enabling a debate around discourses on rural masculinities.